Analisis hamburan kuantum menggunakan diagram Feynman untuk kasus teori ϕ3 - Septian Adhi Nugroho; Asep Yoyo Wardaya; Dwi P. Sasongko (Youngster Physics Journal, 2017)
Scattering is the most important key in particle physics. Quantum field theory/ QFT discusses much about scattering of the particles which are reviewed in any dimensions and depend on the lagrangian forms. In this ϕ theory research, lagrangian concept along with the Green function become its based on the calculation of the generating function of Z[J]. The function is a generator when we analyze the forms of Feynman diagram. In the process of the calculation, we will have an infinite series. That function is used to determine the drawing of Feynman diagrams consist of the vertices and propagators. So that the form of diagram may be able to be analyzed. In this research, there will obtain an infinite series which has to be cut to second order for simplicity case. In the first order, we will obtain 2 types of diagram and in the second one we have 8 types of diagram. There are 10 types of the diagram in total which consist of 7 types of connected diagram and 3 types of disconnected diagram.Keywords: scattering, QFT, lagrangian, Green function Feynman diagram, vertice, propagator, infinite series